2022
DOI: 10.3390/jmse10060732
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effectiveness of Fisheries Policy: A Biological Observation of Species Johnius belengerii in Xiamen Bay

Abstract: The rapid development of China’s economy has brought tremendous pressure to the marine ecosystem, and about 57% of marine fish populations have been overexploited or collapsed. A series of fisheries policies have been implemented successively to improve the decline of resources. Over the past decade, the fisheries sector has particularly increased focus on resource and ecosystem sustainability, which has led to the wider use of stock management policies in China. Therefore, fishery resource assessment is cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As Xiamen is a pilot city of the United Nations, the governance of its coastal zone must focus on the protection and use of marine resources [63,64,[81][82][83]; for example, the restoration of fishery resources and marine species [84]. However, the interviewees said that the artificialization of the coastal zone has left organisms with no place to hide.…”
Section: Ecological Landscapementioning
confidence: 99%
“…As Xiamen is a pilot city of the United Nations, the governance of its coastal zone must focus on the protection and use of marine resources [63,64,[81][82][83]; for example, the restoration of fishery resources and marine species [84]. However, the interviewees said that the artificialization of the coastal zone has left organisms with no place to hide.…”
Section: Ecological Landscapementioning
confidence: 99%
“…During the rapid economic development process in the surrounding waters of the Jimei Peninsula, various issues have emerged [87] , including sedimentation in the ocean [88] , heavy metal pollution [89,90] , reduction in species diversity [91] , habitat compression for protected animals [39] , embryonic deformities in fish [92,93] , overfishing [94] , as well as concerns regarding residents' health [95,96] and food safety [91,97] . As a pilot city recognized by the United Nations, Xiamen's coastal governance must focus on the protection and utilization of marine resources [17,23,36,37,98] , aiming to enhance positive outcomes such as the recovery of fishery resources and the restoration of marine species [99].…”
Section: Natural Ecological Degradation: Imbalance In Governancementioning
confidence: 99%
“…The effectiveness of fisheries policies was evaluated by Huang et al [5], who collected the biological information (length composition, length-weight relationship, growth, mortality, sexual maturity, and feeding intensity) of Johnius belengerii in Xiamen Bay in two Acknowledgments: The author wishes to thank all the contributors to and reviewers of this Special Issue.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The results, in addition to showing indicators of demographic expansion (which was affected by the Pleistocene glacial cycles) and human introduction, highlighted the possible dispersal routes of P. pelagicus throughout Southeast Asia. In the second study [5], an analysis of partial sequences from the mitochondrial control region allowed the authors to determine the population genetic structure, phylogeography and historical demography of Portunus sanguinolentus in East Asia. The results suggested that several past and present habitat configurations have shaped the genetic patterns of P. sanguinolentus to date.…”
mentioning
confidence: 99%